Bayesian network meta-analysis of efficacy and safety of neoadjuvant therapy for non-small-cell lung cancer. (November 2020) - Ren, Yijiu; Tang, Hai; Zhang, Jie; She, Yunlang; Sun, Xiaoting; Xie, Dong; Chen, Chang
Objective: Neoadjuvant chemotherapy has increased the survival benefit of non-small cell lung cancer (NSCLC) patients. The effects of different neoadjuvant therapies are still controversial. We carried out the study to evaluate the efficacy and safety of neoadjuvant therapy. Methods: We performed a search of electronic databases (PubMed, Embase, MEDLINE, Cochrane) for randomized controlled trials (RCTs) comparing neoadjuvant treatment. After literature screening and data extraction, efficacy, and safety were analyzed by the Bayesian network meta-analysis (NMA). Results: A total of 19 RCTs were included, covering 3276 patients and six kinds of neoadjuvant therapies, including immunotherapy, targeted therapy, chemotherapy drugs and radiotherapy. Erlotinib, the first-generation epidermal growth factor receptor t﻿yrosine inhibitors (EGFR TKIs), neoadjuvant targeted therapy is best for improving overall survival (OS) and progression-free survival (PFS), which is superior to other neoadjuvant therapy, such as neoadjuvant chemotherapy with platinum drugs [hazard ratio (HR) 0.39, 95% confidence intervals (CIs) 0.16–0.96], neoadjuvant chemoradiotherapy (HR 0.37, 95% CI 0.14–0.96) and neoadjuvant chemotherapy with non-platinum drugs (HR 0.25, 95% CI 0.07–0.90). OS of all neoadjuvant therapies is superior to surgery alone, but only neoadjuvant chemotherapy with platinum drugs showed a significant advantage (HR 0.76, 95% CI 0.59–0.93). Besides, for the stage IIIA N2 NSCLC patients, no significant difference was found between neoadjuvant therapies. Conclusions: Targeted neoadjuvant therapy is the best treatment for prolonging PFS. The neoadjuvant chemotherapy with platinum drugs was associated with the better OS benefits for patients with NSCLC, compared with surgery alone. There is no significant difference in the efficacy of neoadjuvant therapy for the stage IIIA N2 NSCLC.